Pengaruh Makroekonomi terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Mediasi pada Perusahaan LQ45 - Budiman, Johny; Rudiyanto, Rudiyanto (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The purpose of this study was to investigate the role of macroeconomics by proxies for inflation, interest rates, exchange rates and unemployment rates in influencing firm value with capital structure as a mediating variable in LQ45 companies on the Indonesia Stock Exchange. The objects in this study were 28 LQ45 companies for 5 years, 2017-2021, using a data collection technique, namely purposive sampling, to obtain a sample of 140 data. The method used in testing the data is panel regression analysis. The result of this test is that inflation has a significant positive effect on firm value. The form of inflation that can support the results of this investigation is creeping inflation, where inflation is identified by a slow increase in prices because it is less than 10% per year, has a small percentage and is a relatively long term. Based on this type of inflation, investors will be more interested in investing due to the volatility of trading in commodity prices. Other independent variables such as interest rates, exchange rates and unemployment rates do not have a significant impact on firm value. Then all the independent variables studied have no significant effect on firm value which is mediated by capital structure.